Beyond the Dependency Culture: People, Power and Responsibility by James Robertson, Twickenham, England: Adamantine Press Limited, 1998, 217 pp. (American Journal of Islam and Society, 1999)
James Robertson is a seasoned policy maker. More than three decades ago,from the corridors of Whitehall, he became the architect of the "winds ofchange" theme for British Prime Minister Harold Macmillan's end-of-empiretour of Africa. Robertson's theme of change is a call for liberation, and morespecifically, liberation from the control and domination of institutional power.He sees it fit to argue that in the post-imperial world, prosperity and survivalof nations and peoples depends on a deep-rooted concern for humans andnature.In the postmodern world where communism has breathed its last and socialismis in disrepute, Robertson has attempted to chart a new course for the futureof humanitv. lie believes that both caQ.italism and socialism have served themotives of big businesses and state. It is time for a postmodern worldview toemerge that will rectify the excesses of the two dominant systems. The authorcalls for a new path of progress, based on co-operative self-reliance rather thanincreased dependency, so that the world allows people (and nations) to takeresponsibility for their own development in co-operation with one another. Hesees this not only as an important end in itself, but also as "the only means, barringworldwide catastrophe, of transforming today's ecologically destructivepatterns of human activity into ways of life that can be sustained into thefuture" (p. xi).This theme constitutes the bulk of lectures and papers that are reprinted inthe book. Spanning a period of nearly two decades - from 1977 to 1996 -they complement the author's earlier published works: The Sane Alternative ...